Thermodynamic Properties of Matrine in Citric Acid Solution - Pu, X.H.; Li, Z.X.; Zhao, W.W. (Asian Journal of Chemistry, 2011)
The enthalpies of dissolution of matrine in citric acid solution (0.15 mol L-1) were measured using a RD496-2000 Calvet Microcalorimeter at 309.65 K under atmospheric pressure. The differential enthalpy (ΔdifHm) and molar enthalpy (ΔsolHm) of dissolution of matrine in citric acid solution (0.15 mol L-1) were determined. The corresponding kinetic equation described the dissolution process was elucidated to be . Moreover, the half-life, ΔsolHm, ΔsolGm and ΔsolSm of the dissolution process were also obtained. This work will provide a potential reference for the clinical application of matrine.